Ambiente Memphis: Estágio Atual - Werner, Cláudia M. L.; Travassos, Guilherme H.; Rocha, Ana Regina C. da; Cima, Alberto M. de; Vilanova, Luciana de O.; Coelho, Ana Cecília B.; Alenquer, Paulo L. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1997)
This work presents the current version of the MEMPHIS Environment, developed at COPPE/UFRJ. The MEMPHIS Environment is a Reuse Based Software Engineering Environment that uses TABA's Instantiated Environments Model. The environment was built in Sun workstations with the Unix system and the Eiffel programming language.